Green and efficient biosynthesis of indigo from indole by engineered myoglobins. Issue 58 (26th September 2018) - Liu, Can; Xu, Jiakun; Gao, Shu-Qin; He, Bo; Wei, Chuan-Wan; Wang, Xiao-Juan; Wang, Zhonghua; Lin, Ying-Wu
Abstract : Myoglobin (Mb) was redesigned to a green and efficient biocatalysts for the biosynthesis of indigo from indole, exhibiting improved yield, catalytic efficiency and chemoselectivity (as high as ∼80%). Abstract : With the demand nowadays for blue dyes, it is of practical importance to develop a green and efficient biocatalyst for the production of indigo. The design of artificial enzymes has been shown to be attractive in recent years. In a previous study, we engineered a single mutant of sperm whale myoglobin, F43Y Mb, with a novel Tyr-heme cross-link. In this study, we found that it can efficiently catalyze the oxidation of indole to indigo, with a yield as high as 54% compared to the highest yield (∼20%) reported to date in the literature. By further modifying the heme active site, we engineered a double mutant of F43Y/H64D Mb, which exhibited the highest catalytic efficiency (198 M −1 s −1 ) among the artificial enzymes designed in Mb. Moreover, both F43Y Mb and F43Y/H64D Mb were found to produce the indigo product with a chemoselectivity as high as ∼80%. Based on the reaction system, we also established a convenient and green dyeing method by dyeing a cotton textile during the biosynthesis of indigo, followed by further spraying the concentrated indigo, without the need of strong acids/bases or any reducing agents. The successful application of dyeing a white cotton textile with a blue color further indicates that the designed enzyme and the dyeing method have practical applications in the future.